Preoperative fasting practices in adult elective surgery patients at Charlotte Maxeke Johannesburg academic hospital - Herbst, Julie-Ann Melissa Elizabeth (My University, 2016)
The literature describing the implementation of the latest preoperative fasting guidelines by South African health care professionals is limited. Preoperative fasting of adult patients in the health care system has been observed to be unnecessarily long. Prolonged preoperative fasting may result in detrimental effects such as hypovolaemia, dehydration, headache and hypoglycaemia. These effects impact upon patient wellbeing and satisfaction with healthcare. The aim of this study was to describe preoperative fasting practices in adult elective surgery patients at CMJAH. A prospective, contextual, descriptive study design was used in this study. A sample size of 62 adult patients who required anaesthesia for elective surgery estimated the mean instructed and actual fasting times to an accuracy of within 0.5%. The researcher collected data on the day of surgery using a standardised data collection sheet. The study included 64 patients from four surgical disciplines. The median instructed fasting time was 10 hours with a minimum of 8 hours and a maximum of 12 hours. The mean actual fasting time was 14.92 (S.D. 2.50) hours. The difference between the actual and instructed fasting times was statistically significant. There was however no difference in fasting times between the four surgical disciplines. The mean instructed and actual fasting times for adult elective surgery patients at CMJAH were longer than the recommended guidelines. The mean actual fasting time compared closely with local paediatric and international adult studies suggesting that prolonged preoperative fasting is a widespread problem.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg, 2016
Keywords: Preoperative Fasting; Adult Patients; Surgery